Electron transport pathways in isolated chromoplasts from Narcissus pseudonarcissus L. (7th May 2019) - Grabsztunowicz, Magda; Mulo, Paula; Baymann, Frauke; Mutoh, Risa; Kurisu, Genji; Sétif, Pierre; Beyer, Peter; Krieger‐Liszkay, Anja
Summary: During daffodil flower development, chloroplasts differentiate into photosynthetically inactive chromoplasts having lost functional photosynthetic reaction centers. Chromoplasts exhibit a respiratory activity reducing oxygen to water and generating ATP. Immunoblots revealed the presence of the plastid terminal oxidase (PTOX), the NAD(P)H dehydrogenase (NDH) complex, the cytochrome b 6 f complex, ATP synthase and several isoforms of ferredoxin‐NADP + oxidoreductase (FNR), and ferredoxin (Fd). Fluorescence spectroscopy allowed the detection of chlorophyll a in the cytochrome b 6 f complex. Here we characterize the electron transport pathway of chromorespiration by using specific inhibitors for the NDH complex, the cytochrome b 6 f complex, FNR and redox‐inactive Fd in which the iron was replaced by gallium. Our data suggest an electron flow via two separate pathways, both reducing plastoquinone (PQ) and using PTOX as oxidase. The first oxidizes NADPH via FNR, Fd and cytochrome b h of the cytochrome b 6 f complex, and does not result in the pumping of protons across the membrane. In the second, electron transport takes place via the NDH complex using both NADH and NADPH as electron donor. FNR and Fd are not involved in this pathway. The NDH complex is responsible for the generation of the proton gradient. We propose a model for chromorespiration that may also be relevant for the understanding of chlororespiration and for the characterization of the electron input from Fd to the cytochrome b 6 f complex during cyclic electron transport in chloroplasts. Significance Statement: Chromorespiration takes place via two pathways, one depends on FNR, ferredoxin, the cytochrome b6f complex, and the other depends on the NDH complex and is ferredoxin independent. We propose an electron transport via the cytochrome b6f complex that involves neither a Q‐cycle nor a high potential electron transport chain